PERANCANGAN PASAR AHAD DI KERTAK HANYAR - Nabila, Agil Ayu; Dahliani, Dahliani (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
Pasar Ahad Kertak Hanyar is a traditional market that has evolved from the Dutch East Indies era. Pasar Ahad was established in 2005 through a cooperation with the Build-to-Sell (BGS) system, between the Banjar district government and PT Seraba Kawa which ended in 2023. The condition of the Ahad market building is increasingly concerning, especially the number of dead spaces in the market layout that have been abandoned by traders as a result of buyer behavior. The behavior of buyers tends to follow the main route or easily accessible route and the behavior of traders tends to adjust and can interfere with the comfort of buyers. In other words, there is a correlation between spatial layout and user behavior that can affect the sustainability of space functions. The design of Ahad Market in Kertak Hanyar emphasizes the spatial aspects and affordability. The Behavioral Architecture approach was chosen as the basis for understanding user behavior in space to create a spatial layout by the principles of behavioral architecture. The concept of Connectivity is present as a dialectical representation of users with space that serves as the basis for design improvements. The layout with a linear circulation system results from the connectivity of physical and visual concepts in the market building.